Drivers of household and agricultural adaptation to climate change in Vietnam. (16th March 2021) - Duffy, Colm; Pede, Valerien; Toth, Gregory; Kilcline, Kevin; O'Donoghue, Cathal; Ryan, Mary; Spillane, Charles
ABSTRACT: Vietnam accounts for 6% of global rice production and is exceptionally vulnerable to the impacts of climate change. This study utilises a mixed model ordinal logistic regression on farm household data collected in the Mekong and Red River deltas with the goal of quantifying their impacts on 'planned', in anticipation of gradual climate change, and 'response', to deal with the impacts of sudden onset change, adaptations. The study highlights increased planned adaptation in response to both direct and indirect climate stress. Farm households with higher proportions of income from agricultural sources were more likely to implement planned adaptation measures, but also response level adaptation due to the vulnerability of income sources to sudden onset shock. Planned adaptation is positively influenced by access to training and on farm support, while both planned, and response adaptation were more likely when households had access to financial assistance. Diversity, in terms of revenue sources, increased planned adaptation implementation, but lowered the likelihood of farm households implementing response level adaptation. Institutional support plays a key role in both planned and response adaptation. To increase resilience, it is essential that this support be responsive to localised contextual challenges.